High School EFL Teachers' Identity and Their Emotions Towards Language Requirements - Julio César Torres-Rocha (Universidad Nacional de Colombia, 2017)
This is a study on high school English as a foreign language Colombian teacher identity. Using an interpretive research approach, I explored the influence of the National Bilingual Programme on the reconstruction of teacher identity. This study focuses on how teachers feel about language requirements associated with a language policy. Three instruments were used to collect the data for this research: a survey to find out teachers' familiarity with the policy and explore their views on the language policy and language requirements and other aspects of their identity; autobiographical accounts to establish teachers' trajectories as language learners and as professional English teachers; and semi-structured interviews to delve into their feelings and views on their language policy and requirements for English teachers.